GEMARKAN: Edukasi Gerakan Makan Ikan untuk Mencegah Stunting - Andini, Khansa Luthfia; Pratama, Yendi Hanggara; Chairunnisa, Siti Zahra; Azrarefa, Renata; Suparman, Helvy Aulia; Purnamaningtias, Hadyssa Liftianah; Dianah, Rosyda (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Stunting, a chronic nutritional problem caused by lacking nutritional intake over a prolonged period, particulary during the First 1000 Days of Life (1000 HPK), remains a significant challenge in Indonesia. In Bogor Regency, the prevalence reaches 18.9%, largely due to the low consumption of animal protein. Objective:  This community service points to increase the knowledge and awareness of the community in Sukaharja Village, Bogor Regency, regarding the importance of nutritional fulfillment by promoting the Fish Eating Movement (GEMARIKAN) to prevent stunting. Method: Involving 25 participants (mothers/women in reproductive age), the activity utilized a four-stage process (Planning, Preparation, Implementation, Evaluation). The method includes interactive nutrition education (presentations/videos) assessed by pre/post-tests, supplemented by a cooking demonstration (Pepes Ikan Lele Kemangi) and recipe book distribution. Result: The results of the quantitative evaluation demonstrated a significant increase in the respondents' nutritional knowledge scores after the intervention. Although an improvement in attitude was observed, the changes were not significant. The program successfully met its participant target and fully documented all activities. Conclusion: This program is a vital intervention that tackles high stunting rates by leveraging catfish, a local food source. This by delivering targeted education that successfully boosts knowledge, it is expected to positively influence consumption behaviors and mitigate stunting risk.